Cork stoppers as an effective sorbent for water treatment: the removal of mercury at environmentally relevant concentrations and conditions - Lopes, Claudia B; Oliveira, Joana R; Rocha, Luciana S; Tavares, Daniela S; Silva, Carlos M; Silva, Susana P; Hartog, Niels; Duarte, Armando C; Pereira, E (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2014)
The technical feasibility of using stopper-derived cork as an effective biosorbent towards bivalent mercury at environmentally relevant concentrations and conditions was evaluated in this study. Only 25 mg/L of cork powder was able to achieve 94 % of mercury removal for an initial mercury concentration of 500 mu g/L. It was found that under the conditions tested, the efficiency of mercury removal expressed as equilibrium removal percentage does not depend on the amount of cork or its particle size, but is very sensitive to initial metal concentration, with higher removal efficiencies at higher initial concentrations. Ion exchange was identified as one of the mechanisms involved in the sorption of Hg onto cork in the absence of ionic competition. Under ionic competition, stopper-derived cork showed to be extremely effective and selective for mercury in binary mixtures, while in complex matrices like seawater, moderate inhibition of the sorption process was observed, attributed to a change in mercury speciation. The loadings achieved are similar to the majority of literature values found for other biosorbents and for other metals, suggesting that cork stoppers can be recycled as an effective biosorbent for water treatment. However, the most interesting result is that equilibrium data show a very rare behaviour, with the isotherm presenting an almost square convex shape to the concentration axis, with an infinite slope for an Hg concentration in solution around 25 mu g/L.
Keywords: Cork; Ionic competition; Kineticmodelling; Mercury; Metal removal; Recycling; Sorption

Permeability of Cork for Water and Ethanol - Fonseca, Ana Luisa; Brazinha, Carla; Pereira, Helena; Crespo, João G.; Teodoro, Orlando M. N. D. (Journal of Agricultural and Food Chemistry, 2013)
Transport properties of natural (noncompressed) cork were evaluated for water and ethanol in both vapor and liquid phases. The permeability for these permeants has been measured, as well as the sorption and diffusion coefficients. This paper focuses on the differences between the transport of gases? relevant vapors and their liquids (water and ethanol) through cork. A transport mechanism of vapors and liquids is proposed. Experimental evidence shows that both vapors and liquids permeate not only through the small channels across the cells (plasmodesmata), as in the permeation of gases, but also through the walls of cork cells by sorption and diffusion as in dense membranes. The present study also shows that cork permeability for gases was irreversibly and drastically decreased after cork samples were exposed to ethanol or water in liquid phase.
doi: 10.1021/jf4015729doi: 10.1021/jf4015729The following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; diffusion; permeability; sealing properties; Sorption; water transport